Electrical insulation breakdown and its theory, process, and prevention : emerging research and opportunitites - Du, Boxue, 1961- (Engineering Science Reference, 2019)
"This book examines the latest developments in high voltage insulation breakdown. It explores the influence of space charge accumulation on aging processes of polymeric insulating materials, electrical treeing due to imperfections in the insulations such as impurities, voids, defects, and other related topics"-- Provided by publisher.
Keywords: Electric insulators and insulation -- Defects.; Breakdown (Electricity) -- Prevention.; elektronické knihy; electronic books